POLITICAL CHALLENGES IN A GLOBALIZED WORLD: POLITICAL PARTIES - Orhan, Ertuğrul Buğra (My University, 2022)
One of the most important concepts explaining the rapid change in the world is globalization. The important topic behind the power of this concept to explain change is undoubtedly the economy. The economic transformation confronts the states, which are the most important actors of the modern political system, with great difficulties. Therefore, the research aims to explain the challenges facing the state and political parties by globalization. In this context, the theories developed on the concepts of political parties are discussed and the negative effects of globalization in economic, political and social aspects are discussed. The discussion is in the inductive conceptualization pattern in terms of method. The research reveals that political parties will make difficult choices between the interests of global corporations and the demands of citizens. In addition, the weakening of the ability of states to use economic instruments reduces the possibility of political governments to realize their economic and political goals. Failure to meet social demands may also make the legitimacy of political parties questionable. This result shows that the theories about the decline of political parties may still be valid.
Keywords: Globalization; political parties; nation state; political legitimacy